Diseño metodológico para la investigación de las rutas de estudio y aprendizaje. Reporte de investigación - Gil Chaves, Diana; Sánchez, Neila (Revista Científica, 2011)
What aspects can be considered when definite methodologies approach the paths at study and learning of seventh grade students in several schools in Bogota? Even, taking in to account the proportionality in the class room? What research instruments can contribute to complexity analysis in the class room? Answering the previous questions is the main intention at this document. It’s the product of a several year research experience in the methodology building as a part of the research process. These analyses are based on the complexity of the class room’s culture.